PENYULUHAN TENTANG PENCEGAHAN DAN PENULARAN HIV/AIDS PADA SISWA/I SMP KERTHA WISATA TEGALALANG GIANYAR - A.A.S. Sawitri; P. Cintya D.Y; L. Seriani; P. Aryani; W. Weta (Buletin Udayana Mengabdi, 2012)
Bali is known as the second highest province for HIV and AIDS prevalence in Indonesia. HIV reported that cases have been increased from 1,253 in 2007 to 3,778 in 2010, while 40% cases occurred among teenagers (20-29 years old). One factor probably contributing was lack of knowledge on HIV which might increase their risky behavior. Recent data showed that only 14.3% teenagers could answer properly about HIV Prevention and knew the common misperception of HIV spreading. Gianyar Regency which is the most visiting domestic and foreign tourists in Bali, accounted for 142 HIV cases and 20 deaths until October 2010. Health Promotion about Prevention of HIV and AIDS among students of SMP Kertha Wisata in Taro village Gianyar Regency, which is the field project of Udayana University, was held to improve the knowledge level of teenager on HIV and AIDS. The health promotion was given by teaching, discussion, games, and giving brochures and poster about prevention of HIV and AIDS. The evaluation done by comparing pretest and post-test result among audiences showed that the increasing level of knowledge from 64% to 87%. It proves that giving information about HIV and AIDS is one of the effective ways to improve the knowledge about HIV and AIDS.